Rationale for CDR132L, an antisense inhibitor of miR-132, for a novel therapy for ventricular remodelling after myocardial infarction. (14th October 2021) - Aimo, A; Iborra Egea, O; Bayes-Genis, A; Passino, C; Emdin, M
Abstract: Background: Heart failure (HF) development is a common complication of myocardial infarction (MI), which warrants a search for novel therapies able to prevent left ventricular remodelling after an MI. CDR132L is a synthetic antisense inhibitor of miR-132. In a pig model of reperfused MI, monthly intravenous administration of CDR132L proved safe and effective in preventing HF development. They expect CDR132L to have an additive, and possibly synergistic, effect to standard-of-care therapies (beta-blockers, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers [ACEi/ARB], and mineralocorticoid receptor antagonists [MRA]) because of their distinct first targets. Nonetheless, a degree of overlap in the final effects of CDR132L and current therapies might exist, given that ACEi/ARB and MRA ultimately modulate myocardial inflammation and fibrosis, as CDR132L do. We assessed this point by searching for similar changes in protein expression between MI therapies and CDR132L. Methods: We retrieved the 14 mRNAs significantly altered in the myocardium of pigs receiving CDR132L compared with control pigs: BMPR2, ADRA1D, GCLC, CD44, PRDX1, ECM1, LEP, GATA3, GPX1, EIF4G1, ACE2, HMOX1, RTN4 and LIFR. Except for RTN4, all these mRNAs were downregulated by CDR132L. We assumed a close correlation between changes in mRNA levels and the expression of the corresponding proteins. By using massive public databases, such as Drugbank, the Open Targets Platform and the Human Protein Atlas, we identified all approved, investigational and experimental drugs reported to modulate the expression of at least one of these 14 proteins in any setting. Results: We did not find any drug modulating more than one of the 14 proteins. Therefore, no drug, including ACEi/ARB or MRA, proved able to mimic the effects of CDR132L on protein expression. Conclusions: CDR132L might have an additive or synergistic action to standard drugs, given the different effects on protein expression profiles. CDR132L might then help prevent post-MI remodelling even on top of optimal medical therapy. This point should be verified in dedicated studies. FUNDunding Acknowledgement: Type of funding sources: None.